Zdolność kredytowa a ocena ratingowa jednostek samorządu terytorialnego - Łosiewicz, Ewa (The Local Government's Credit Ability versus Rating Evaluation, 2006)
This paper presents the local government's specificity as the banking clients and the problem of credit ability. The trends of local government's financial need show that it will be a bigger and more important client for commercial banks in the nearest futures. But decreasing rate of revenue points to rising credit risk of the local government. A good mark of economical position of local government is rating of the independent agency, but for a small institution it is too expansive. The proposition of internal rating of local government instead of credit ability evaluation prepared by banks is presented in the article. The banks should give less risky credits and the clients - local governments should get bigger credibility out of the bank for lower cost
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1109, s. 403-408